177Lu-DOTATATE therapy in metastatic/inoperable pheochromocytoma-paraganglioma - Sanjeet Kumar Jaiswal; Vijaya Sarathi; Saba Samad Memon; Robin Garg; Gaurav Malhotra; Priyanka Verma; Ravikumar Shah; Manjeet Kaur Sehemby; Virendra Patil; Swati Jadhav; Anurag Lila; Nalini S. Shah; et al. (2020)
Introduction: 177 Lu-DOTATATE-based peptide receptor radionuclide therapy (PRRT) is a promising therapy for metastatic and/or inoperable pheochromocytoma and paraganglioma (PPGL). We aim to evaluate the efficacy and safety of and identify predictors of response to 177 Lu-DOTATATE therapy in metastatic and/or inoperable PPGL. Methods: This retrospective study involved 15 patients of metastatic or unresectable PPGL, who received 177 Lu-DOTATATE PRRT therapy. Clinical, biochemical (plasma-free normetanephrine), and radiological (anatomical and functional) responses were compared before and after the last therapy. Results: A total of 15 patients (4 PCC, 4 sPGL, 5 HNPGL, 1 PCC + sPGL, 1 HNPGL + sPGL) were included. The median duration of follow up was 27 (range: 11–62) months from the start of PRRT. Based on the RECIST (1.1) criteria, progressive disease was seen in three (20%), stable disease in eight (53%), partial response in one (7%), and minor response in three (20%) and controlled disease in 12 (80%). On linear regression analysis the presence of PGL ( P = 0.044) and baseline SUV max >21 ( P < 0.0001) were significant positive predictors of early response to PRRT. Encouraging safety profiles were noted with no long term nephrotoxicity and hematotoxicity. Conclusion: 177 Lu-DOTATATE therapy is an effective and safe modality of treatment for patients with metastatic/inoperable PPGL. Although it is not prudent to withhold PRRT in metastatic PPGL with baseline SUV max < 21, baseline SUV max >21 can be used to predict early response to PRRT.